Trends of Carnivore protoparvovirus 1 and Canine morbillivirus infection in domestic dogs in South Africa - Quan, Melvyn (University of Pretoria, 2023)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2022.